Evolving Trends in Kidney Cancer - Kommu, Sashi S.; Gill, Inderbir S.; Kommu, Sashi S.; Gill, Inderbir S. (IntechOpen, 2020)
Kidney cancer imposes a significant cancer burden and its incidence continues to rise globally. Mortality in advanced kidney cancer remains high despite oncological, surgical and multimodal optimisation. Genetic associations, heterogeneity and limitations in early diagnosis through lack of optimal biomarkers add to the challenges. Over the last two decades there has been an exponential increase in diagnostic and therapeutic advances in the management of kidney cancer. The coupling of scientific advances in engineering and technology with oncological therapeutics has recently ushered a renewed optimism. The role of minimally invasive approaches through focal therapy and surgical extirpation using the robotic platform has been unprecedented and paramount. Virtual augmentation and mixed reality platforms have proved useful supplementary tools in surgical planning. The role of surgical simulation and training in development of surgeons with the optimal skill set is essential to provide optimal care. This book is the first in a series that explores the evolving trends in kidney cancer. The focus of the book is broad and includes topics ranging from immunotherapy to surgical simulation. Some chapters explore leading edge concepts while others capture the evolving trends and future concepts. The Editors aim to stimulate the readers to explore the key concepts and to encourage research and innovation along the main themes presented.
English
Keywords: Urology & urogenital medicine; Urology & urogenital medicine